From cognitive to emotional: The social and emotional learnig in portuguese schools - Martins Matos, Teresa (Aprender, 2025)
Social and emotional education has increasingly established itself as a key component of contemporary education, promoting well-being, academic success, and inclusion. This article critically analyses the trajectory of social and emotional learning (SEL) in Portugal between 2017 and 2025, based on a systematic review of the literature, institutional reports, and programmes implemented in school contexts. Ten programmes developed in public schools and municipalities were selected, with emphasis on projects such as Devagar se Vai ao Longe, MindSerena, Atitude Positiva, PDPSC, and ADN Socioemocional 2.0. Evidence points to positive impacts in areas such as emotional self-regulation, self-esteem, empathy, relational competences, and school climate. However, structural challenges remain, such as the absence of a national framework, limited teacher training in this field, and the need for sustainable public policies. The discussion relates the data to the main theoretical models, highlighting the transformative potential of social and emotional learning when integrated in a systemic and participatory manner. Future directions are also indicated, including the urgency of structural investment, continuous teacher training, and the development of longitudinal research.